Pembelajaran Pendidikan Agama Hindu Dengan Model Discovery Learning Dalam Penguatan Profil Pelajar Pancasila Pada Siswa Kelas VII Di SMP Negeri 3 Singaraja Tahun Ajaran 2024/2025 - Leni, Ketut; Sanjaya, Putu; Prapnuwanti, Ni Luh Purnamasuari (Guna Widya: Jurnal Pendidikan Hindu, 2025)
This study aims to understand the learning of Hindu Religious Education using the Discovery Learning model in Strengthening the Pancasila Student profile in grade VII students at SMP Negeri 3 Singaraja, Buleleng District, Buleleng Regency. The theories used to analyze the formulation of the problem are cognitive learning theory, constructivist learning theory and contextual learning theory. This research is a type of fenomenology research with a descriptive research approach. The result of this study relate to the form of learning using discussion methods and the question and answer methods. The process of learning Hindu Religious Education using the discovery learning model in strengthening the profile of Pancasila student is carried out through six stages; 1. Stage of providing (stimulation), 2. Stage of stating or identifying problem (problem statement), 3. Stage of collecting data (data collection), 4. Stage of processing data (data processing), 5. Stage of proving (verification), and 6. Stage of drawing conclusions or generalizations (generalization). The implications of learning Hindu Religious Education using the discovery learning model are the implications of divine values, implications of human values, implications of school image, and implications of learning in cognitive, affective and psychomotor aspects.